Molecular assessment of differences in the duodenal microbiome in subjects with irritable bowel syndrome - Giamarellos-Bourboulis, Evangelos; Tang, Jie; Pyleris, Emmannouil; Pistiki, Aikaterini; Barbatzas, Charalambos; Brown, Jordan; Lee, Clarence C; Harkins, Timothy T; Kim, Gene; Weitsman, Stacy; Barlow, Gillian M; Funari, Vincent A; et al. (Scandinavian journal of gastroenterology, 2015)
Breath testing and duodenal culture studies suggest that a significant proportion of irritable bowel syndrome (IBS) patients have small intestinal bacterial overgrowth. In this study, we extended these data through 16S rDNA amplicon sequencing and quantitative PCR (qPCR) analyses of duodenal aspirates from a large cohort of IBS, non-IBS and control subjects. Consecutive subjects presenting for esophagogastroduodenoscopy only and healthy controls were recruited. Exclusion criteria included recent antibiotic or probiotic use. Following extensive medical work-up, patients were evaluated for symptoms of IBS. DNAs were isolated from duodenal aspirates obtained during endoscopy. Microbial populations in a subset of IBS subjects and controls were compared by 16S profiling. Duodenal microbes were then quantitated in the entire cohort by qPCR and the results compared with quantitative live culture data. A total of 258 subjects were recruited (21 healthy, 163 non-healthy non-IBS, and 74 IBS). 16S profiling in five IBS and five control subjects revealed significantly lower microbial diversity in the duodenum in IBS, with significant alterations in 12 genera (false discovery rate < 0.15), including overrepresentation of Escherichia/Shigella (p = 0.005) and Aeromonas (p = 0.051) and underrepresentation of Acinetobacter (p = 0.024), Citrobacter (p = 0.031) and Microvirgula (p = 0.036). qPCR in all 258 subjects confirmed greater levels of Escherichia coli in IBS and also revealed increases in Klebsiella spp, which correlated strongly with quantitative culture data. 16S rDNA sequencing confirms microbial overgrowth in the small bowel in IBS, with a concomitant reduction in diversity. qPCR supports alterations in specific microbial populations in IBS.